Efektivitas Model Pembiayaan Pendidikan Sentralistik dan Desentralistik - Nur Atika Alias; Zian Salsabila Bidaula (Journal of Public Policy Analys, 2024)
This study aims to analyze the effectiveness of centralized and decentralized education financing in improving the quality of education. This study uses quantitative research methods with secondary data analysis from various sources. The results of the study indicate that decentralized education financing is more effective in improving the quality of education compared to centralized financing. This is due to the flexibility of budget management and greater community participation in decision making. However, centralized financing has advantages in terms of efficiency and uniformity of education standards. This study recommends the need for a combination of the two financing systems to achieve optimal education quality. Some types of centralized education financing models are the Faudation plan model , the power equalizing plan model , the model of choice and voucher plans , and the full state funding model . While the types of decentralized financing models include the Pure Fund Assistance Model, the Planning Basis Model, the Tax Guarantee Principal Planning Model, and the Diverse Funding Source Model.